A carbon-quantum-dot-hybridized NiOx hole-transport layer enables efficient and stable planar p–i–n perovskite solar cells with high open-circuit voltage. Issue 36 (10th August 2021) - Xia, Xuefeng; Zhang, Dan; Wang, Xiaofeng; Xiao, Zonghu; Li, Fan
Abstract : A novel CQD-hybridized NiO x HTL is developed to improve the efficiency and stability of planar p–i–n PSCs. Abstract : In recent years, the nickel oxide (NiO x )-based planar p–i–n perovskite solar cell (PSC) has progressed rapidly. Nevertheless, poor electrical properties of NiO x, unoptimized band alignment between NiO x and perovskites, as well as pervasive defects and unwanted chemical redox reactions at NiO x /perovskite interfaces have severely limited the device efficiency and stability. It is of particular interest to explore a facile approach to address these issues simultaneously. Herein, an effective carbon-quantum-dot-hybridized NiO x (CQD-hybridized NiO x ) hole transport layer (HTL) is fabricated via hybridizing a kind of environmentally friendly CQD with NiO x . By virtue of the rich surface polar groups of CQDs, hybridization of such CQDs with NiO x can efficaciously upgrade the electrical properties of NiO x HTLs, thereby reducing ohmic loss and energy level offset at NiO x /perovskite interfaces. Meanwhile, the application of CQD-hybridized NiO x HTLs can boost the nucleation and growth of perovskite layers, thus suppressing the formation of interfacial defects/traps and reducing interface-mediated nonradiative recombination losses. Moreover, such CQD-hybridized NiO x HTL can also diminish redox reactions at the NiO x /perovskite interface, improving interface stability. Based on this CQD-hybridized NiO x HTL, a champion PCE of 20.53% with enhanced stability has been achieved. More strikingly, the optimized device delivers a V oc as high as 1.16 V, the highest V oc for CH3 NH3 PbI3 PSCs based on NiO x HTLs as far as we know. These results demonstrate that CQD-hybridized NiO x HTLs will be a promising candidate for efficient and stable planar p–i–n PSCs.